2018 Vegetable Production Handbook Chapter 1: Commercial Vegetable Production in Florida - Josh H. Freeman; Peter J. Dittmar; Gary E. Vallad (EDIS)
This 2-page fact sheet is chapter 1 of the 2018 Vegetable Production Handbook. The objective of this publication is to provide updated information on crop cultivars, pesticide labels, and certain practices for vegetable production in Florida. Suggested practices are guidelines for growers to plan farm activities and are always subjected to review using the latest scientific data available. Written by Josh H. Freeman, Peter J. Dittmar, and Gary E. Vallad, and published by the Horticultural Sciences Department, 2018.